EFFECT OF WORK ENVIRONMENT AND COMMUNICATION ON EMPLOYEE PERFORMANCE AT PT ARYAN INDONESIA - Jeffry H. Sinaulan; Hilda Aulia (Fakultas Bisnis dan Ilmu Sosial Universitas Dian Nusantara, 2022)
Abstract: This study aims to determine, describe, and analyze the influence of the work environment and communication on employee performance variables in a company. Either Simultaneously or Partially. The results showed that the work environment and communication variables had a significant effect on employee performance variables. Based on the t-test, the t-count value = 9.878 with a significance value of 0.000 <0.05 for the Work Environment Variable, and the t-count = 4.831 with a significance value of 0.001 <0.05 for the Communication Variable. The Work Environment Variable has a greater influence on Employee Performance with a Regression Coefficient of 0.844 compared to the Communication Variable of only 0.318. From the overall results of the study, it can be concluded that the Work Environment and Communication Variables have a significant influence on the Employee Performance Variables either Simultaneously or Partially. Keyword: Work Environment, Communication, Employee Performance